ANALISIS HAMBATAN BELAJAR SISWA PADA MATERI PERSAMAAN TRIGONOMETRI - Aulia Khairunnisa; Elah Nurlaelah; Sumanang Muhtar Gozali (Journal on Mathematics Education Research (J-MER), 2022)
In learning activities at school students often have difficulty solving math problems, especially during the process of solving math problems. Teachers must know the difficulties that students have when solving a mathematical problem in learning at school. The Aim of this study is to analyze student learning barriers in the material of trigonometric equations in 11th grade of senior high school. This research was conducted in one of the senior high schools in Lampung. The subjects of this study were students in that school. The type of research used in this research is descriptive qualitative research. The data collection technique in this study is a written test and students interview. The data obtained were collected and then analyzed using descriptive analysis, by describing the results of student answers in the form of errors in answering test questions. The results showed that students had difficulties in understanding concepts, principles and operations on the material of trigonometric equations.Keywords: learning obstacle, student difficulties, trigonometric equations